2010
DOI: 10.1055/s-0030-1247133
|View full text |Cite
|
Sign up to set email alerts
|

Current Strategy for Staging and Treatment: The BCLC Update and Future Prospects

Abstract: Staging and treatment indication are relevant topics in the management of patients with hepatocellular carcinoma (HCC) and for optimal results, they have to take into account liver function, tumor stage, and physical status. For any staging system to be meaningful it has to link staging with treatment indication; this should be based on robust scientific data. Currently, the sole proposal that serves both aims is the Barcelona Clinic Liver Cancer (BCLC) approach. It takes into account the relevant parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
832
1
19

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,008 publications
(861 citation statements)
references
References 116 publications
(169 reference statements)
9
832
1
19
Order By: Relevance
“…Under our surveillance practices, patients received a regular ultrasound abdominal scan and serum alpha‐fetoprotein on a 6 monthly schedule or more frequently as deemed necessary by the patient's physician. Staging of HCC was assessed using the Barcelona Clinic Liver Cancer (BCLC) classification 16. Type of treatment provided for the HCC was categorized into surgical curative, local ablative, systemic chemotherapy, and best supportive care.…”
Section: Methodsmentioning
confidence: 99%
“…Under our surveillance practices, patients received a regular ultrasound abdominal scan and serum alpha‐fetoprotein on a 6 monthly schedule or more frequently as deemed necessary by the patient's physician. Staging of HCC was assessed using the Barcelona Clinic Liver Cancer (BCLC) classification 16. Type of treatment provided for the HCC was categorized into surgical curative, local ablative, systemic chemotherapy, and best supportive care.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of liver disease affects the prognosis as well as the chosen treatment, and the type of treatment can have a significant impact on the prognosis. 1 Over the years, several groups have developed different systems or scores for stratifying HCC patients [2][3][4][5][6][7][8][9] ( Table 1). Most of these classifications have resulted from analyses of the association of clinical or pathological parameters with survival.…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24][25] In addition to these prospective validations, several studies have demonstrated the ability of the model. 26,27 It has been recently endorsed by numerous groups 1,21,28 and is included in the guidelines for the management of HCC from the American Association for the Study of Liver Diseases. 29 Other staging systems such as the CLIP system have also been externally validated.…”
Section: Formentioning
confidence: 99%
“…I read with interest the article by Wang et al (1) regarding the comparison between cryoablation and radiofrequency ablation (RFA) in the management of small hepatocellular carcinoma (HCC). The authors demonstrated that cryoablation had lower local tumor progression than RFA.…”
Section: To the Editormentioning
confidence: 99%
“…(1) Indeed, with improved devices and techniques, many studies have reported encouraging results, including complete ablation and survival rates of RFA in treating HCC lesions >3 cm. (2,3) In our study, patients with incomplete ablation after two sessions of the same technique were considered treatment failures and were further treated by percutaneous ethanol injection, microwave, RFA, cryoablation, or surgery, as appropriate.…”
Section: Replymentioning
confidence: 99%